Effect of Feeding Programs on Broilers Cobb and Arbor Acres plus Performance - Saki, A.A.; Momeni, M.; Tabatabaei, M.M.; Ahmadi, A.; Rahmati, M.M.H.; Matin, H.R. Hemati; Janjan, A. (International Journal of Poultry Science, 2010)
The main objective of this study was to determine the effects of various feeding programs (with different energy protein levels) and strain on broiler performance. Three hundred ninety six day old chicks were used in this study. The treatments groups were designed in a 2 x 3 factorial with two commercial strains (Cobb and Arbor Acres Plus) and three dietary programs 1) NRC regimen 2) Single diet (S) and 3) Phase Feeding Regimen (PF). Traits such as fed intake, feed conversion ratio, body weight, production index, mortality and growth rate were recorded for strains and feeding programs. At the end of period there were no significant effects between strains in mentioned traits. But for NRC and PF feed intake was significantly lower than S diet (p